Pengaruh Media Video Animasi terhadap Peningkatan Hasil Belajar Ipas pada Siswa Kelas V SD Negeri Lamklat - Nurbaiti; Lili Kasmini; Raziska Ibrahimi (Jurnal Ragam Pengabdian, 2026)
This Study aims to determine the influence of animated video media on improving the learning outcomes of IPAS in grade V students of SD Negeri Lamklat. Improving learning is a challenge for teachers in presenting material that is interesting and easy for students to understand. One of the ways that can be done is to use innovative and creative learning media such as animation video media. This study uses a quantitative approach with a quasi-experimental type of research. This research will be carried out in December 2025. The subject of this study is class V which consists of two classes, namely the experimental class and the control class. The date collected using learning outcome tests in the form of pretest and posttest and analyzed using SPSS. The results of this study show that the use of animated video media in the learning process has a effect on improving the learning outcomes of IPAS students in grade V of SD Negeri Lamklat, this is evidenced by the average score of student learning outcomes in the experimental class which was previously treated from 51.4 to 90.52 while in the control class that only used conventional methods from 51.8 to 90.32. Thus, it can be concluded that animation video media has a significant effect on improving the learning outcomes of IPAS students in grade V of SD Negeri Lamklat. The implications of this research can be a reference for teachers to use animated video media as an effective alternative learning media to improve student learning outcomes.